Women and Christian mission: ways of knowing and doing theology - Adeney, Frances S. (Missional church, public theology, world Christianity, 2015)
"What are Christian women thinking about mission? How do they do mission? What informs their knowledge and action as they address issues in a complex world where religious proselytizing has become suspect? This empirical study explores those questions, finding congruence among women from diverse backgrounds and cultural contexts. Women in mission face common identity issues, utilize art and beauty in their work, and develop character as they overcome obstacles in their cultural and denominational settings. Through nearly one hundred interviews of women in Europe, Asia, Brazil, and the United States, a study of women's theologies of mission, lectures, and countless conversations with women around the globe, this study finds common themes among contemporary women doing Christian mission." --